ANTILITHIASIS EFFECTIVENESS TEST OF ETHANOL EXTRACT OF ALANG-ALANG (Imperata cylindrica (L.) Beauv) ON WHITE RATS (Rattus novergicus) - Stenly Komansilan; Rolef Rumondor (Indonesian Biodiversity Journal, 2021)
The purpose of this study was to determine the antilithiation effectiveness of alang-alang extract in white rats by looking at the histology of the rat kidney. The study design, the treatment group was divided into 5 groups. Control group (P0), ethylene glycol group (P1), Hydrochlorothiazide treatment group (P2), alang-alang extract group at a dose of 100 mg/kgBW (P3), and alang-lang extract group at a dose of 200 mg/kgBW (P4). The results showed that alang-alang extract had activity in repairing the kidneys of white rats with urolithiasis. And the alang-alang extract dose of 200 mg/kgBW has better effectiveness.